IMPLEMENTATION OF MORAL VALUES TOWARDS PROSPECTIVE ACCOUNTANTS PERCEPTION OF ACCOUNTING STUDENTS EMPIRICAL STUDY ACCOUNTING PROGRAM STUDENTS FACULTY OF ECONOMICS NURTANIO UNIVERSITY BANDUNG - Mulyana, Asep; Waruwu, Fotuho; Rahmawati, Mia (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2023)
Abstract This research aims that moral values are very important insupporting the career of an accountant who has high credibility so thathe is responsible for his profession because the profession of anaccountant is very tempting from deviant behavior towards theprofession so that he is equipped with moral ethics and obedience toreligion contained in good morals. taught by religion, thereforeprospective accountant students have a fear of sin if they commitdeviations and they are responsible to God who is all-seeing for allactivities carried out in every activity of an accountant. With this fear,they are protected from the characteristics of Satan. who plunged himinto the abyss of sin on the path of the corrupt accounting professionand became a person who is honest and has noble character. Themethod used in this research is by using quantitative methods, namelyinterviews and observations, distributing questionnaires, the object ofwhich is students of the accounting study program at NurtanioUniversity, Bandung. The conclusion from the results of this researchis that the influence of moral values on prospective accountants showsexemplary honesty in all activities in the organization, especially theaccounting profession. Because the ethical values of prospectiveaccountants must be upheld as a basis for trust for their clients.Keywords: Moral Values, Prospective Accountants